A Mendelian randomization study of the effect of tea intake on breast cancer - Deng, Yuqing; Ge, Wenxin; Xu, Huili; Zhang, Jiaming (Frontiers in Nutrition, 2022)
Background: The relationship between tea consumption and risk of breast cancer is inconsistent in previous observational studies and is still in dispute. We intended to detect the causal association between tea consumption and breast cancer risk using a two-sample Mendelian randomization (MR) analysis. Methods: The summary statistics of tea consumption was obtained from the UK Biobank Consortium with 349,376 individuals and breast cancer was from the Breast Cancer Association Consortium (122,977 cases and 105,974 non-cases). Sensitivity analyses of evaluating the influence of outliers and pleiotropy effects were performed by a variety of MR methods under different model assumptions. Results: After potentially pleiotropic single nucleotide polymorphisms (SNPs) excluded using MR Pleiotropy RESidual Sum and Outlier method, the odds ratios of per extra daily cup of tea intake for overall, estrogen receptor (ER)-positive, and ER-negative breast cancer risk was 1.029 (95% confidence interval (CI)=0.983-1.077, P=0.2086), 1.050 (95% CI=0.994-1.109, P=0.078) and 1.081 (95% CI=0.990-1.103, P =0.6513), respectively. The results were consistent with sensitivity analysis that excluding SNPs associated with other phenotypes, manifesting that the findings were convincing and robust. Moreover, in the multivariable MR analysis, the null associations for breast cancer risk remained after the adjustment for smoking and alcohol consumption separately or together. Conclusion: Our MR results based on genetic data did not support a causal relationship between tea consumption and breast cancer risk.